Learning about good nutrition with the 5-color front-of-package label“Nutri-Score”: an experimental study - Robin C. Hau; Klaus W. Lange (Food Science and Human Wellness)
The Nutri-Score is a 5-color front-of-pack nutrition label designed to provide consumers with an easily understandable guideline to the healthiness of food products. The impact that the Nutri-Score may have on consumers’ choices is unclear since different experimental paradigms have found vastly different effect sizes. In the present study, we have investigated how student participants change a hypothetical personal 1-day-dietary plan after a learning phase during which they learn about the Nutri-Scores of the available food items. Participants were instructed to compose a healthy diet plan in order that the question of whether the Nutri-Score would improve their ability to compose a healthy dietary plan could be investigated, independent of the question of whether they would apply this knowledge in their ordinary lives. We found a substantial (Cohen’s d = 0.86) positive impact on nutritional quality (as measured by the Nutrient Profiling System score of the Food Standards Agency) and a medium-sized (Cohen’s d = 0.43) reduction of energy content. Energy content reduction was larger for participants who had initially composed plans with higher energy content. The results suggest that the Nutri-Score has the potential to guide consumers to healthier food choices. It remains unclear, however, whether this potential will be reflected in real-life dietary choices.